An Electron Microscopic Study on the Effects of Prostaglandin F2a (PG F2a) and Fenugreek Extract on Thymocytes in Thymus Gland - Al-Kaisy, K. S. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
This study was done to clarify the effects of PGF2a on thymocytes in rat thymus gland, and the possibility of minimizing its effects by using fenugreek extract. The results have shown that PGF2a can cause a considerable degenerative changes in thymocytes. On the other hand,the fenugreek extract enhances the thymocyte proliferation and at least minimizes the effects of PGF2a on thymocytes.